Langerhans cell histiocytosis: unusual bone marrow infiltration—report of 2 cases in Ecuador - Santana, Paulina; Arias-Intriago, Marlon; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2024)
Langerhans cell histiocytosis (LCH) is a histiocytic neoplasm characterized by the abnormal proliferation of Langerhans cells. Bone marrow (BM) involvement is associated with high-risk disease and poor survival. Although BM involvement is particularly uncommon, no reported cases of LCH with BM infiltration have been documented in Latin America until now.The aim of this report is to highlight the clinical, hematological, and BM findings of two cases of LCH with BM infiltration, providing insights that may aid in detecting suspected patients.We present two cases of LCH with BM infiltration. One case involved a 23-month-old male patient, and the other a 16-month-old female patient. Common clinical findings in both cases included hepatosplenomegaly and fever. Hematological findings revealed anemia in both cases. The key diagnostic tool was the BM biopsy, which revealed histiocyte nests with characteristic morphology, CD1a-positive cells, increased eosinophils, and reactive paratrabecular lymphocytes. This report underscores the significance of clinical profiles in predicting BM infiltration in LCH.The presence of histiocyte nests displaying the characteristic morphology of Langerhans cells, accompanied by an elevation in eosinophils, indicates bone marrow involvement.Furthermore, the demonstration of CD1a-positive cells through immunohistochemistry serves as a crucial diagnostic tool.